Analisis Kualitas Isi dalam Teks Berita detiknews.com Edisi Januari 2024 sebagai Referensi Bahan Ajar Kelas XI SMA - Esti Maurilla; Firas Abid Zidan; Rizna Asticka; Savira Nailil Hana; Syafira Oktavia Pramesti; Asep Purwo Yudi Utomo; Riyadi Widhiyanto (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research is motivated by the tendency of news today to pay less attention to the 5W+1H elements (What, Who, Why, When, Where, and How) which are explained according to the concept of objectivity and effectiveness of news and information. The purpose of this study is to analyze the quality of information in the detik.news January 2024 edition. This analysis focuses on information quality, data availability, efficiency, and objectivity. This study is based on “Detiknews.Com News Text January 2024 Edition” and data collection techniques with the goal of learning, analyzing, and documenting. The analytic techniques used are qualitative and quantitative. In data collection, we used a formal data collection method that included the use of a symbol (or symbol) and a collection method. The purpose of using this qualitative deskriptif method is to analyze verbal phrases found in detiknews.com articles. The findings of this study may be seen in relation to the number of stories that have been published on detiknews.com, namely whether they have high quality images with clear and easy-to-understand text. The purpose of news reporting is to report on current events without revealing any personal information. The quality of information found on detik.news is intended to be useful in determining whether a piece of information is reliable in terms of language, objectivity, effectiveness, and the extent to which it has been disseminated to the public.